Changes in quality of life and health across the first two years of the COVID-19 pandemic: A mixed methods, longitudinal study of older adults - Andrea Huseth-Zosel, Ph.D.; Heather R. Fuller, Ph.D. (Archives of Gerontology and Geriatrics Plus)
The objective of this study was to identify shifts in older adults’ well-being over the first two years of the COVID-19 pandemic. Between March 2020 and April 2022, 76 adults aged 65+ from the upper Midwest participated in telephone interviews across five timepoints. Quantitative and qualitative questions focused on perceptions of QOL, physical health and mental health, as well as changes over the two years of interviews. Repeated measures ANOVAs indicated significant changes in self-reported QOL over time, but no significant changes to self-reported physical or mental health. Thematic content analysis revealed relevant themes for each content area. Findings provided a longitudinal view of changes in perceived QOL and health among older adults during the COVID-19 pandemic. Despite quantitative improvements in QOL and stability in health, qualitative themes indicated nuances impacts including challenges to physical activity and fluctuations in mental health and QOL.